Parents' perception about the factors that causes obesity among children At Innovation Center and Quality Unit Hospital Jitra / Siti Rozidah Hashim - Hashim, Siti Rozidah (2011)
Obesity is one of the most common chronic diseases in childhood. Because of that , this research was carry out to know the awareness of the causes and factors that causes the in increase obesity among children. This study only to parents who have child between the ages of 5 to 12 years. It is based on the questionnaire form, that was circulated around the Outpatient Department came from different socioeconomic were chosen as sample. This survey is in descriptive manner and all data obtained were analyzed using the SPSS (statistical Package for Social Sciences, Version 18.0) and AMOS (Analysis of Moments Structures) software. Result shows that most parents believe that obesity among children are caused by genetic factors and poor diet. Parents' perception also believe, obesity is caused by the increase in technology that cause most of the time children spend watching television and video games than doing sports activities